Learning of sequences of finger movements and timing: frontal lobe and action-oriented representation. - Sakai, K; Ramnani, N; Passingham, R (2002)
Motor sequence learning involves learning of a sequence of effectors with which to execute a series of movements and learning of a sequence of timings at which to execute the movements. In this study, we have segregated the neural correlates of the two learning mechanisms. Moreover, we have found an interaction between the two learning mechanisms in the frontal areas, which we claim as suggesting action-oriented coding in the frontal lobe. We used positron emission tomography and compared three learning conditions with a visuo-motor control condition. In two learning conditions, the subjects learned either a sequence of finger movements with random timing or a sequence of timing with random use of fingers. In the third condition the subjects learned to execute a sequence of specific finger movements at specific timing; we argue that it was only in this condition that the motor sequence was coded as an action-oriented representation. By looking for condition by session interactions (learning vs. control conditions over sessions), we have removed nonspecific time effects and identified areas that showed a learning-related increment of activation during learning. Learning of a finger sequence was associated with an increment of activation in the right intraparietal sulcus region and medial parietal cortex, whereas learning of a timing sequence was associated with an increment of activation in the lateral cerebellum, suggesting separate mechanisms for learning effector and temporal sequences. The left intraparietal sulcus region showed an increment of activation in learning of both finger and timing sequences, suggesting an overlap between the two learning mechanisms. We also found that the mid-dorsolateral prefrontal cortex, together with the medial and lateral premotor areas, became increasingly active when subjects learned a sequence that specified both fingers and timing, that is, when subjects were able to prepare specific motor action. These areas were not active when subjects learned a sequence that specified fingers or timing alone, that is, when subjects were still dependent on external stimuli as to the timing or fingers with which to execute the movements. Frontal areas may integrate the effector and temporal information of a motor sequence and implement an action-oriented representation so as to perform a motor sequence accurately and quickly. We also found that the mid-dorsolateral prefrontal cortex was distinguished from the ventrolateral prefrontal cortex and anterior fronto-polar cortex, which showed sustained activity throughout learning sessions and did not show either an increment or decrement of activation.